Problematika Pembelajaran BTQ di SMK Pemuda Krian - Faris Ahmad; Imam Fauji (PAI RAFAH, 2024)
This research aims to analyze the problematics of BTQ learning at SMK Pemuda Krian, both from internal and external factors. The research method used is descriptive qualitative with data collection through interviews, observation, and documentation. The results showed that internal factors affecting the ability to read the Qur'an of class X DKV students include student motivation, intelligence, and interest and talent in the pronunciation of Arabic letters. The main obstacles faced are difficulties in pronouncing hijaiyah letters according to makhraj, limited basic knowledge of makharijul huruf and tajweed, and the influence of local dialects. Influential external factors include the family environment, parental support, and teacher teaching methods. Efforts and strategies implemented by SMK Pemuda Krian to overcome these obstacles include regular practice programs and special classes, dialectical approaches and basic training in makharijul huruf, theory classes and practical tajweed exercises, and the provision of adequate learning resources. This study concludes that these various factors and strategies greatly affect students' ability to read the Qur'an properly and correctly.